1993
DOI: 10.1007/bf00309096
|View full text |Cite
|
Sign up to set email alerts
|

Solitary hamartomatous duodenal polyp; a different entity: Report of a case and review of the literature

Abstract: Solitary hamartomatous duodenal polyps are a clinical entity considered until now to express an incomplete or initial form of Peutz-Jeghers syndrome (PJ syndrome). Following our experience of 1 case, we analyzed the clinical characteristics of the 12 previously reported cases of solitary hamartomatous duodenal polyps. In none of these cases did we find any documentation of mucocutaneous pigmentation, a family or personal history of intestinal polyps, or local neoplastic degeneration of the disease, and all cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 7 publications
1
31
0
Order By: Relevance
“…Solitary PJ-type polyps, defined as hamartomatous polyps without any of the clinical symptoms of PJS, are characterized histologically by tree-like branching of smooth muscle fibers, with a core of smooth muscle, covered by mucosal tissue of nearnormal appearance [4] . It is truly difficult to determine whether these solitary duodenal hamartomatous polyps are an incomplete type or initial clinical manifestation of PJS [2] . This entity may be differentiated from PJS based on information from previous studies, including: the lack of perioral or perianal mucocutaneous pigmentation and lack of family history; symptom onset usually occurring past the sixth and seventh decades of life; and lower risk of local cancer development than hamartomatous polyps in patients with PJS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Solitary PJ-type polyps, defined as hamartomatous polyps without any of the clinical symptoms of PJS, are characterized histologically by tree-like branching of smooth muscle fibers, with a core of smooth muscle, covered by mucosal tissue of nearnormal appearance [4] . It is truly difficult to determine whether these solitary duodenal hamartomatous polyps are an incomplete type or initial clinical manifestation of PJS [2] . This entity may be differentiated from PJS based on information from previous studies, including: the lack of perioral or perianal mucocutaneous pigmentation and lack of family history; symptom onset usually occurring past the sixth and seventh decades of life; and lower risk of local cancer development than hamartomatous polyps in patients with PJS.…”
Section: Discussionmentioning
confidence: 99%
“…A search of case reports on the MEDLINE database up to 2014 using the terms "solitary", "duodenum", and "hamartomatous polyp", but without PJS, identified 19 patients in 13 studies published in English with solitary-PJ type polyps in the duodenum, including the patient described here [2,[5][6][7][8][9][10][11][12][13][14][15] (Table 1). Age at onset ranged from 23-89 years (mean ± SD: 60.3 ± 20.1 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a patient with a Peutz-Jeghers polyp without either mucocutaneous pigmentation or a positive family history was described as a case of solitary Peutz-Jegherstype hamartomatous polyp. It has been suggested that this condition should be considered as a clinical entity different from Peutz-Jeghers syndrome [2] . A solitary Peutz-Jegherstype hamartomatous polyp is histologically characterized by tree-like branching of smooth muscle fibers, with a core of smooth muscle, covered by mucosal tissue of near-normal appearance [3] .…”
Section: Introductionmentioning
confidence: 99%
“…A solitary Peutz-Jegherstype hamartomatous polyp is histologically characterized by tree-like branching of smooth muscle fibers, with a core of smooth muscle, covered by mucosal tissue of near-normal appearance [3] . A solitary Peutz-Jeghers-type hamartomatous polyp in the duodenum is rare, and few reports have described its characteristic endoscopic features [2,[4][5][6][7][8][9][10] . We describe three cases of solitary Peutz-Jeghers-type hamartomatous polyp and their endoscopic findings in detail.…”
Section: Introductionmentioning
confidence: 99%